PENGARUH BRAND AWARENESSS, BRAND ASSOCIATION DAN PERCEIVED QUALITY TERHADAP PURCHASE INTENTION DENGAN MEDIASI BRAND EQUITY PADA PRODUK BAN IRC DI CV. RAJAWALI INTI SUKSES - Lawrence Faith Setiawan (Jurnal Performa)
The purpose of this research is to explain and identify the effect of brand awareness, brand association, and perceived quality on brand equity, as well as the effect of brand equity as mediation on purchase intention.The sample of 148 people have the role as respondents in this research, by using non-probability technique and purposive sampling method. Respondents that are qualified and can fill out the survey that are the consumers of CV. Rajawali Inti Sukses. The survey process is done through online questionnaire distribution by using Google form with 22 statements items. Likert scale with the range of 1 to 5 is used as measurement parameter. This research uses quantitative method with the help of SMARTPLS software. The benefit of this research is to identify branding factors that can be applied in the company in increasing purchase intention. The result of this research indicates that brand awareness, brand association, perceived quality affect brand equity and brand equity affects significantly on consumer purchase intention. This research utilizes the result of the research as reference base for making company decision.